Duplex Schemes in Multiple Antenna Two-Hop Relaying. (6th April 2008) - Unger Unger, Timo Timo; Klein Klein, Anja Anja
Abstract : A novel scheme for two-hop relaying defined as space division duplex (SDD) relaying is proposed. In SDD relaying, multiple antenna beamforming techniques are applied at the intermediate relay station (RS) in order to separate downlink and uplink signals of a bi-directional two-hop communication between two nodes, namely, S1 and S2. For conventional amplify-and-forward two-hop relaying, there appears a loss in spectral efficiency due to the fact that the RS cannot receive and transmit simultaneously on the same channel resource. In SDD relaying, this loss in spectral efficiency is circumvented by giving up the strict separation of downlink and uplink signals by either time division duplex or frequency division duplex. Two novel concepts for the derivation of the linear beamforming filters at the RS are proposed; they can be designed either by a three-step or a one-step concept. In SDD relaying, receive signals at S1 are interfered by transmit signals of S1, and receive signals at S2 are interfered by transmit signals of S2. An efficient method in order to combat this kind of interference is proposed in this paper. Furthermore, it is shown how the overall spectral efficiency of SDD relaying can be improved if the channels from S1 and S2 to the RS have different qualities.